2022
DOI: 10.3390/ijerph19148666
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Style and Its Relationships with Early Memories of Separation Anxiety and Adult Separation Anxiety Symptoms among Emerging Adults

Abstract: Emerging adulthood concerns the transition from adolescence to adulthood. It foresees the separation from the family and the creation of new significant relationships, whereby specific attachment styles might be triggered when facing these challenges. The present study investigates the influence of retrospective memories associated with childhood separation anxiety symptoms upon emerging adults’ romantic avoidant vs. anxious attachment styles including adult separation anxiety symptoms as mediators. Age and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…It is argued that emerging adults with early separation anxiety memories or anxious attachment style will have higher separation anxiety scores, however, avoidant attachment does not affect ASAD. In Bassi et al, about 400 Italian emerging adults were recruited for this study, which aimed to investigate how the symptoms of separation anxiety and retroactive memory affect insecure attachment types in emerging adults [11]. Three self-report questionnaires were utilised to get data from the participants.…”
Section: Attachment and Separation Anxiety In Adultsmentioning
confidence: 99%
“…It is argued that emerging adults with early separation anxiety memories or anxious attachment style will have higher separation anxiety scores, however, avoidant attachment does not affect ASAD. In Bassi et al, about 400 Italian emerging adults were recruited for this study, which aimed to investigate how the symptoms of separation anxiety and retroactive memory affect insecure attachment types in emerging adults [11]. Three self-report questionnaires were utilised to get data from the participants.…”
Section: Attachment and Separation Anxiety In Adultsmentioning
confidence: 99%
“…Additionally, a few studies indicated that the loss of a parent in youth may delay efforts to achieve future intimacy due to the fear of losing the partner (e.g., Walter & McCoyd, 2009), and that being in an emotional relationship may arouse separation anxiety (Bögels et al., 2013). Furthermore, it was reported that ASA and the memories of early separation anxiety were positively related to anxious attachment, and that ASA mediated the relationship between childhood separation anxiety and anxious attachment (Bassi et al., 2022). Finally, in a recent study (Yurtseven & Özkul, 2022), a positive association was found between the fearful, preoccupied, and dismissive attachment subscale scores and ASA, while a negative association was found between ASA and secure attachment.…”
Section: Introductionmentioning
confidence: 99%